The Role of Bhabinkamtibmas Through Counseling to High School Students to Reduce Drug Abuse Cases in the Legal Area of Polri Magelang - Tambunan, Elia Prima (Advances in Police Science Research Journal, 2024)
At present the crime of drug abuse is very concerning, the cases handled by the Magelang Police since 2019-2022 have always increased every year. There are even cases of drug abuse where the perpetrators are students and the number has increased from 2019-2022. The Polri institution through Bhabinkamtibmas has a significant role and is expected to be able to suppress drug abuse crimes through pre-emptive and preventive actions by conducting outreach to the community, especially students who are the next generation of the nation. This research method is a type of descriptive analysis research with a qualitative approach. Data collection techniques in the form of interviews, observation/observation, and document study. Based on the analysis of the problems that have been carried out, based on Bhabinkamtibmas’ knowledge, the Magelang Police do not yet have adequate provisions to carry out guidance and counseling. Efforts that can be made are improving the management of the implementation of counseling activities by bhabinkamtibmas, collaboration with drug detectives. In terms of the ability to carry out counseling, not all personnel have sufficient ability to carry out their duties so that there is a need for increased ability, especially in the field of communication, and an appreciation is needed so that the expectations expected are formed. work attitude. It can be concluded that Bhabinkamtibmas activities in carrying out outreach have been carried out but are not in accordance with procedures and still need to be improved. Based on the research indicators, it is explained that the competencies possessed by bhabinkamtibmas are inadequate and need to be improved.